2010
DOI: 10.1007/s00284-010-9648-8
|View full text |Cite
|
Sign up to set email alerts
|

PCR Detection of Thermophilic Spore-Forming Bacteria Involved in Canned Food Spoilage

Abstract: Thermophilic bacteria that form highly heat-resistant spores constitute an important group of spoilage bacteria of low-acid canned food. A PCR assay was developed in order to rapidly trace these bacteria. Three PCR primer pairs were designed from rRNA gene sequences. These primers were evaluated for the specificity and the sensitivity of detection. Two primer pairs allowed detection at the species level of Geobacillus stearothermophilus and Moorella thermoacetica/thermoautrophica. The other pair allowed group-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Spores are formed if bacteria experience environmental conditions that are deleterious to growth, such as nutrient limitation, and when conditions are again suitable for growth, the spore germinates to form a vegetative cell that begins to proliferate (Cook & Pierson, 1983;Santo & Doi, 1974). As spores are highly resistant to heat sterilization and to various drugs, control of spores of food poisoning bacteria, such as Clostridium botulinum (Abgueguen et al, 2003), Clostridium perfringens (Valenzuela-Martinez et al, 2010), and Bacillus cereus (Granum & Lund, 1997), and food and beverage spoilage bacteria, such as Bacillus coagulans (Cosentino, Mulargia, Pisano, Tuveri, & Palmas, 1997;Palop, Raso, Pagán, Condón, & Sala, 1999) and Moorella thermoacetica (Prevost, Andre, & Remize, 2010), is an extremely important problem in food and beverage preservation (Brown, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Spores are formed if bacteria experience environmental conditions that are deleterious to growth, such as nutrient limitation, and when conditions are again suitable for growth, the spore germinates to form a vegetative cell that begins to proliferate (Cook & Pierson, 1983;Santo & Doi, 1974). As spores are highly resistant to heat sterilization and to various drugs, control of spores of food poisoning bacteria, such as Clostridium botulinum (Abgueguen et al, 2003), Clostridium perfringens (Valenzuela-Martinez et al, 2010), and Bacillus cereus (Granum & Lund, 1997), and food and beverage spoilage bacteria, such as Bacillus coagulans (Cosentino, Mulargia, Pisano, Tuveri, & Palmas, 1997;Palop, Raso, Pagán, Condón, & Sala, 1999) and Moorella thermoacetica (Prevost, Andre, & Remize, 2010), is an extremely important problem in food and beverage preservation (Brown, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The model was developed for Clostridium botulinum, Geobacillus stearothermophilus and Bacillus cereus; C. botulinum was chosen as the pathogenic bacteria which has to be considered in priority in a risk assessment of aseptic-UHT-type products (Codex Alimentarius Commission, 1993a), B. cereus was included as a pathogenic bacteria commonly found in milk powder (Becker et al, 1994) and finally, G. stearothermophilus was taken into account because it can survive to very high heat treatment (Rigaux et al, 2013) and has been then often reported as responsible of ambient stable product spoilage (Denny, 1981;Ito, 1981;Prevost et al, 2010). More precisely, André et al (2013) have determined that Geobacillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Thermophilic, spore-forming bacteria, later characterized as M. thermoacetica, were detected in the 1970s in Japan in hot vending machines serving canned coffee with milk, soup, and "shiruko" (sweet beverage made from azuki bean powder), all of which were maintained at 55 to 60°C (8,10,22). This species has also been associated with the spoilage of canned food in other countries (1,14). These contaminants result in strong acidification, abnormal odors and colors, pH decrease, and separation and coagulation of milk components (8,23).…”
mentioning
confidence: 97%